Addressing the Psychosocial Risk Factors Affecting the Developing Brain of the High-Risk Infant - Cynthia Rogers (Washington University Journal of Law & Policy, 2018)
In this article, Cynthia Rogers examines how exposure to prenatal and postnatal psychosocial stressors in the caregiver-infant interaction can lead to impaired brain development. Specifically, Rogers examines how maternal mental health and substance use disorders related to poverty have a deleterious effect on infant outcomes and create dysfunctional parenting styles that continue to negatively impact childhood brain development. Rogers points to intervention programs like the Perinatal Behavioral Health Service at Washington University School of Medicine as a successful tool for screening pregnant and postpartum women for mental health disorders and directing parents of high-risk infants to physicians, social workers, psychiatrists and/or therapists with the goal of improving maternal mental health and optimizing child outcomes. Such programs can have positive impacts on maternal mental health and evidence suggests that these interventions also positively influence childhood brain development.
Keywords: brain development; high-risk infant; psychosocial stressors; poverty; postpartum depression; substance use disorder; maternal mental health; bipolar disorder; premature birth; child language development; NICU; intervention; Medicaid